2021
DOI: 10.1186/s12879-021-06234-0
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotypes and the risk factors associated with multicentric intraepithelial lesions of the lower genital tract: a retrospective study

Abstract: Background Multicentric intraepithelial lesions of the lower genital tract (multicentric lesions) were defined as intraepithelial lesions of two or three sites within cervix, vagina, and vulva occurring synchronously or sequentially. The characteristics of multicentric lesions has been poorly understood. This study aimed to evaluate the risk factors for multicentric lesions, including specific HPV genotypes. Methods A retrospective case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…In our study, comparable percentages of HPV 53 could be identified in HSIL with 8.3%, whereas no HPV 53 was found in LSIL, but 8.3% HPV 53 in CC. Other studies also described frequent detection of the subtype HPV 53 [26,29,30]. Furthermore, HPV 53 is described to occur more likely in multiple infections together with other types [26].…”
Section: Discussionmentioning
confidence: 92%
“…In our study, comparable percentages of HPV 53 could be identified in HSIL with 8.3%, whereas no HPV 53 was found in LSIL, but 8.3% HPV 53 in CC. Other studies also described frequent detection of the subtype HPV 53 [26,29,30]. Furthermore, HPV 53 is described to occur more likely in multiple infections together with other types [26].…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, after adjusting for potential confounding effects, such as age, multiple HPV infections, types of transformation zone, margin status, and preoperative HPV16/18 infection, co-existent CIN2/3 and VaIN had a higher tendency to harbor a persistent HR-HPV infection. This may due to the possible pathogenesis of multicentric lesions in the lower genital tract associated with speci c HPV genotypes infection in the cervix and vagina respectively [25]. Therefore, women suffering from co-existent CIN2/3 and VaIN should be closely followed up in the post-treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concept of multicentric lower genital tract disease is generally accepted, there are some variations or inconsistencies regarding the definition of multicentricity. Several previous studies have defined multicentricity as intraepithelial lesions of two or three sites in lower genital tract, excluding invasive lesions [ 4 , 7 , 14 , 16 , 18 ]. Other research has included any grade of IN or invasive lesions [ 17 , 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%